2017
DOI: 10.1007/s00228-017-2341-0
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen usage correlates with increased risk of Parkinson’s disease in older women with breast cancer: a case–control study in Taiwan

Abstract: Tamoxifen usage was associated with a 3.32-fold increase in the likelihood of having Parkinson's disease among older women with breast cancer in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 79 publications
0
18
0
Order By: Relevance
“…The authors explained the neuroprotective effect of estrogen might be disrupted by tamoxifen therapy [3]. Latourelle et al's finding was partially compatible with Lin et al's study showing a duration-dependent effect of tamoxifen therapy on the risk of Parkinson's disease [2]. That is, the longer the tamoxifen use, the higher the risk of Parkinson's disease.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…The authors explained the neuroprotective effect of estrogen might be disrupted by tamoxifen therapy [3]. Latourelle et al's finding was partially compatible with Lin et al's study showing a duration-dependent effect of tamoxifen therapy on the risk of Parkinson's disease [2]. That is, the longer the tamoxifen use, the higher the risk of Parkinson's disease.…”
mentioning
confidence: 67%
“…One article written by Montastruc et al reported that no association could be detected between tamoxifen therapy and Parkinsonism [1]. On the contrary, Lin et al reported that tamoxifen therapy was associated with a 3.3-fold increased risk of Parkinson's disease among older women with breast cancer in Taiwan [2]. A cohort study by Latourelle et al reported that tamoxifen therapy was associated with a 5-fold increased rate of Parkinson's disease after 4 years of tamoxifen therapy [3].…”
mentioning
confidence: 99%
“…Notably, the use of estrogen receptor antagonists (i.e., tamoxifen) are associated with increased Parkinson's disease risk in women [136][137][138]. However, the role of estrogen receptor antagonists in Alzheimer's disease risk in women is less clear [139][140][141][142][143].…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities were included as follows: alcohol‐related disease, cancer, cardiovascular disease (including coronary artery disease, heart failure, cerebrovascular disease and peripheral atherosclerosis), chronic liver disease (including cirrhosis, hepatitis B infection, hepatitis C infection and other chronic hepatitis), chronic obstructive pulmonary disease and diabetes mellitus. All comorbidities studied were diagnosed based on ICD‐9 codes, which have been well examined in previous studies 21‐25 …”
Section: Methodsmentioning
confidence: 99%